Health providers’ experiences with mental health specialist video consultations in primary care: a qualitative study nested within a randomised feasibility trial - Haun, Markus W.; Hoffmann, Mariell; Wildenauer, Alina; Tönnies, Justus; Wensing, Michel; Szecsenyi, Joachim; Peters-Klimm, Frank; Krisam, Regina; Kronsteiner, Dorothea; Hartmann, Mechthild; Friederich, Hans-Christoph (BMJ open, 2021)
Objective Despite available effective treatments for mental health disorders, few patients in need receive even the most basic care. Integrated telepsychiatry services may be a viable option to increase access to mental healthcare. The aim of this qualitative process evaluation embedded in a randomised controlled feasibility trial was to explore health providers’ experiences with a mental healthcare model integrating mental health specialist video consultations (MHSVC) and primary care. Methods A qualitative process evaluation focusing on MHSVC in primary care was conducted. In 13 semistructured interviews, we assessed the experience of all mental health specialists, primary care physicians and medical assistants who participated in the trial. A thematic analysis, focusing on the implementation, mechanisms of impact and context, was applied to investigate the data. Results Considering (1) the implementation, participants evaluated the consultations as feasible, easy to use and time saving. Concerning (2) the mechanisms of impact, the consultations were regarded as effective for patients. Providers attributed the patients’ improvements to two key aspects: the familiarity of the primary care practice and the fast access to specialist mental healthcare. Mental health specialists observed trustful therapeutic alliances emerging and described their experience as comparable to same-room care. However, compared with same-room care, specialists perceived the video consultations as more challenging and sometimes more exhausting due to the additional effort required for establishing therapeutic alliances. Regarding (3) the intervention’s context, shorter travel distances for patients positively affected the implementation, while technical failures, that is, poor Internet connectivity, emerged as the main barrier. Conclusions MHSVCs in primary care are feasible and successful in improving access to mental healthcare for patients. To optimise engagement and comfort of both patients and health providers, future work should focus on empirical determinants for establishing robust therapeutic alliances with patients receiving MHSVC (eg, leveraging non-verbal cues for therapeutic purposes). Trial registration number DRKS00015812; Results.
Online issue publication November 09, 2021
Gesehen am 22.12.2021